Rose with thorns: Phenomenological study regarding being a preschool teacher in rural areas in Turkey - YAĞAN, SEVCAN (My University, 2019)
The main purpose of this study is to reveal the experiences of pre-school teachers who teach in rural areas. Phenomenology design, which is one of the qualitative research designs, was used in this study. This study included 9 pre-school teachers who performed teaching profession in Diyarbakir, Ordu, Van, Bursa, Sanliurfa and Agri provinces between 2016-2017 educational year. The data of the study were collected via semi-structured interviews which were conducted through the Skype program. The results of this study indicate that teaching in the rural areas gives high level of spiritual satisfaction; on the other hand, it is a difficult process that contributes to professional development of the teachers. Teachers also expressed that they experienced language and communication problems with both parents and children and that they had problems with regard to heating, water, electricity, unsuitable class environments and teaching material deficiencies.

Köy okulunda görev yapan okul öncesi öğretmenlerinin yaşadıkları öğretmenlik deneyimlerini ortaya çıkarmayı amaçlayan bu çalışma nitel araştırma desenlerinden fenomenoloji ile desenlenmiştir. Çalışmaya 2016-2017 eğitim-öğretim yılında, Diyarbakır, Ordu, Van, Bursa, Şanlıurfa ve Ağrı illerine bağlı bir köyde okul öncesi öğretmeni olarak görev yapan 9 okul öncesi öğretmeni katılmıştır. Araştırmanın verileri Skype programı aracılığıyla yapılan yarı yapılandırılmış görüşmeler yoluyla toplanmıştır. Araştırmanın sonucunda köyde öğretmenlik yapmanın manevi tatmini yüksek ancak öğretmenin mesleki gelişimine katkı sağlayan oldukça zorlu bir yolculuk olduğu; köy okullarında öğretmenlerin hem veliler hem de çocuklar ile dil ve iletişim problemleri yaşadığı; ısınma, su, elektrik, uygun olmayan sınıf ortamları ve materyal eksiklikleri olduğu dile getirilmiştir.
Keywords: Preschool Teachers; Teacher Education; Rural Education; Fenomenological Study; Turkey; Okul Öncesi Öğretmenleri; Öğretmen Eğitimi; Kırsal Eğitim; Fenomenolojik Çalışma; Türkiye